Aging and working memory performance: Electrophysiological correlates of high and low performing elderly. (November 2017) - Lubitz, Alexander F.; Niedeggen, Michael; Feser, Maximilian
Abstract: In this study we investigated age-related changes in WM capacity and their respective ERP correlates. We explicitly addressed the differentiation between high and low performing elderly to identify electrophysiological correlates of successful aging. Therefore, ERP and behavioral data was obtained from 45 young (mean = 22.73 years) and 35 older participants (mean = 68.49 years). Both groups performed a visual-spatial n -back task with two levels of difficulty. Additionally, related neuropsychological tests were administered. Older subjects performed less accurately in both conditions of the n -back task. Older age was additionally associated with a reduced fronto-central positivity (labeled as P200) in the 2-back task and an overall reduced amplitude of the parietal positivity (labeled as P300). The latter shifted to frontal leads in older subjects. Additionally, only in the group of the older participants, increased P200 and decreased parietal P300 amplitudes correlated with performance. Regarding older high and low performers, we observed a clear shift of frontal activity of both ERP components in the group of high performers. High performers additionally performed better in spatial working memory, verbal learning, and fluid intelligence tasks. We conclude, that increasing demands of working memory load are accompanied by a reallocation of resources in both young and older adults. With age, executive control and updating processes (indexed by both ERP components) are diminished or rely on more frontal processes for compensation. However, high performing older adults, who perform comparable to young adults, sustain comparable executive control processes, exceeding pure compensation. Highlights: WM tasks of higher complexity rely on more frontal processes. Older age is associated with reduced fronto-central positivity for complex WM tasks. Executive control and updating processes (indexed by ERP components) are reduced with age. Old high performers sustain executive control processes comparable to young adults. Successful aging is therefore a combination of brain maintenance and compensation.